ANTIOXIDANT EFFECT OF TRANS-3 HYDROXYCINNAMIC ACID AGAINST LIVER DAMAGE METHOTREXATE INDUCED IN RATS - Ö. Arslan; F. N. E. Akdemir Dr. Abdurrahman Yurtaslan Education; Research Hospital of Oncology; Ankara; TURKEY (Journal of Animal and Plant Sciences, 2018)
The aim of this study was to determine the possible antioxidant effect of trans-3 hydroxycinnamic acid (HC) as an antioxidant agent against oxidative liver damage induced by MTX in rats. In the present study, the animals were divided into 4 groups of 6 rats in each group. The groups were designated as control, methotrexate (First day-single dose) , HC (5 days-5 consecutive doses) and MTX + HC (First day- MTX single dose and then HC 5 days-5 consecutive dose) . Rats were sacrificed on 5 day of experiment and the liver tissues were removed. Superoxide dismutase (SOD) activity, glutathione (GSH) , and malondialdehyde (MDA) levels were evaluated in the liver tissue samples. MDA levels increased in the MTX group according to control group. But MDA levels decreased significantly in HC group. Also, SOD activity decreased in MTX group according to control group. However, this enzyme activity increased depending on HC group. On the other hand, GSH level in the rat's liver tissue were significantly reduced in MTX group compared to control. In conclusion, HC have an antioxidant effect against oxidative liver damage induced-MTX in rats. derivatives are naturally found in strawberries, plums,
Keywords: Methotrexate; oxidative stress; liver damage; trans-3 hydroxycinnamic acid.